Post-glacial uplift - Wojtal, Steven F. (Oberlin College Library, 1997)
View downstream from the Skogafoss. Skogafoss occurs at a scarp along the southern edge of a glaciated plateau; the base of the waterfall is a wave cut terrace extending to the ocean. The scarp resulted from erosion by waves along the ocean shore. This scarp is currently found several miles from the shoreline. It was eroded immediately following the melting of the ice cap and was later raised significantly above sea level by post-glacial rebound. Compare with image 410.